Physical Education Classes with different durations, and their contribution to Daily Physical Activity Recommendations of Adolescents in Porto, Portugal - Manuela Costa; José Carlos Ribeiro; Maria Paula Silva; Jorge Mota (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: For many adolescents, physical education classes (PE) provide the most relevant opportunity to be engaged in physical activity (PA). Although the evidence suggested low levels of PA in PE few studies have focused their investigation on the contribution of PA performed during PE to daily PA. So, the purpose of this study was to analyze PA levels of adolescents in Porto, Portugal during daily school hours when they attended PE (PED) with 45 min of duration (PED45), PE with 90 min of duration (PED90), school days without PE (NPED) and weekend days (WD). Methods: This study was conducted in four Portuguese public schools with 441 students (253 girls) volunteers, aged between 10 to 18 years (14.31 ± 2.70). PA was assessed using an Actigraph accelerometer for seven consecutive days. Independent and general linear model repeated measures were used to assess differences between PA according to NPED, PED45, PED90 and WD. A logistic regression was used to investigate the contribution of PE to the compliance of adolescents’ daily PA recommendations. Results: PED45 contributed, on average, 16.9% for the daily moderate to vigorous physical activity (MVPA) and PED90 accounted for 32.2%. All students engaged in more MVPA on PED than NPED or WD (p<0.05). PE classes were associated with higher odds to accomplished the recommended 60 min of daily MVPA (OR = 2.66, 95% CI = 2.01-3.53). Conclusion: This study suggested that PE increased the daily MVPA levels and played a considerable role in providing PA to accomplish PA guidelines.